Quality of nursing work life dengan penerapan patient safety pada perawat ruang rawat inap - Ningsih, Harin Oktia; Imallah, Rosiana Nur; Kurniasih, Yuni (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The implementation of patient safety is influenced by the quality of nursing work life. When nurses have a good quality of nursing work life, encompassing the dimensions of work life-home life, work design, work context, and work word, they will be more compliant with patient safety procedures, thereby maintaining the quality of healthcare services. Purpose: To determine the relationship between Quality of Nursing Work Life and the Implementation of Patient Safety among Nurses. Method: This quantitative, descriptive correlation study with a cross-sectional approach was conducted in the Inpatient Ward of PKU Muhammadiyah Gamping Hospital. The sampling technique used purposive sampling, with a sample size of 61 respondents. The research instrument used a questionnaire. Data analysis used the Kendall Tau test. Results: This study shows that the Quality of Nursing Work Life is mostly in the good category (58 respondents (95.1%), and the implementation of Patient Safety is mostly in the good category (59 respondents (96.5%). The data analysis obtained a p-value (p=0.003), with a value of <0.05, indicating a relationship between Quality of Nursing Work Life and the implementation of patient safety among inpatient nurses. Conclusion: Quality of nursing work life influences the implementation of patient safety in inpatient nurses. Keywords: Nurses; Patient Safety; Quality of Nursing Work Life. Pendahuluan: Penerapan patient safety dipengaruhi oleh quality of nursing work life. Ketika perawat memiliki quality of nursing work life yang baik, yaitu mencakup dimensi work life-home life, work design, work context, dan work word, maka perawat akan lebih patuh terhadap prosedur keselamatan pasien sehingga mutu pelayanan kesehatan terjaga. Tujuan: Untuk mengetahui hubungan Quality of Nursing Work Life dengan Penerapan Patient Safety pada Perawat. Metode: Penelitian kuantitatif jenis deskriptif korelasi dengan pendekatan cross sectional yang dilakukan di Ruang Rawat Inap RS PKU Muhammadiyah Gamping. Teknik pengambilan sampel menggunakan Purposive Sampling, jumlah sampel 61 responden. Instrumen penelitian menggunakan kuesioner. Analisa data menggunakan uji Kendall Tau. Hasil: Penelitian ini menunjukan Quality of Nursing Work life sebagian besar dalam kategori baik sebanyak 58 responden (95.1%) dan penerapan Patient Safety sebagian besar responden dalam kategori baik sebanyak 59 responden (96.5%). Hasil analisa data diperoleh nilai (p=0.003) nilai tersebut (<0.05) artinya ada hubungan Quality of Nursing Work Life dengan penerapan patient safety pada perawat ruang rawat inap. Simpulan: Quality of nursing work life mempengaruhi penerapan patient safety pada perawat ruang rawat inap. Kata Kunci: Patient Safety; Perawat; Quality Of Nursing Work Life.